2021
DOI: 10.3389/fmicb.2021.630741
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Patterns of Bacterial Community Structure and Function in Response to Estuarine Output in the Middle of the Bohai Sea

Abstract: Understanding environment-community relationships under shifting environmental conditions helps uncover mechanisms by which environmental microbial communities manage to improve ecosystem functioning. This study investigated the microbial community and structure near the Yellow Sea River estuary in 12 stations across the middle of the Bohai Sea for over two seasons to elucidate the influence of estuarine output on them. We found that the dominant phyla in all stations were Proteobacteria, Cyanobacteria, Bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…Moreover, Gammaproteobacteria was not the major class in this survey area, which was inconsistent with many previous studies [ 19 , 32 , 77 ]. The seasonal pattern of Gammaproteobacteria in the Bohai Sea, reported by Wang et al [ 78 ], which was consistent with our winter data (data not shown), might be the reason. Lack of Chloroflexi in high-salinity waters in our study was in accordance with the hypothesis that origins of pelagic Chloroflexi are likely from soil and sediment habitats, and freshwater habitats harbor the most diverse phylogenetic assemblages in comparison to brackish and marine habitats [ 79 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Gammaproteobacteria was not the major class in this survey area, which was inconsistent with many previous studies [ 19 , 32 , 77 ]. The seasonal pattern of Gammaproteobacteria in the Bohai Sea, reported by Wang et al [ 78 ], which was consistent with our winter data (data not shown), might be the reason. Lack of Chloroflexi in high-salinity waters in our study was in accordance with the hypothesis that origins of pelagic Chloroflexi are likely from soil and sediment habitats, and freshwater habitats harbor the most diverse phylogenetic assemblages in comparison to brackish and marine habitats [ 79 ].…”
Section: Discussionsupporting
confidence: 93%
“…High salinity seemed to have a strong inhibitory effect on riverine bacteria ( 49 51 ), which may inhibit viral production in cells that are derived from upstream estuarine regions. Significant changes in the microbial community structure along environmental gradients were reported for these three estuaries ( 52 54 ). The close nature of the virus-microbe relationship makes it reasonable that shifts in the microbial community composition could lead to corresponding changes in the coexisting viral communities.…”
Section: Discussionmentioning
confidence: 95%
“…Owing to the host-specific natures of viruses, the higher diversity of bacterial communities in winter may be the main reason for the higher α-diversities of the T4-like phages that were observed in winter in the three estuaries. Indeed, the α-diversities of the bacterial communities from YZRE, YRE, and PRE were also significantly higher in winter than in summer, despite the lower bacterial abundances in winter ( 52 54 ). Enhanced vertical mixing and a higher level of nutrients in winter, especially phosphorus, can trigger the activation of some dormant bacterial taxa ( 69 , 70 ), which makes the bacterial community more complex and further promotes the proliferation of their corresponding phages ( 70 , 71 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The increasing anthropogenic activities have caused serious ecological problems to the BS, such as eutrophication, algal blooms, and hypoxia in the bottom water (Song et al, 2016;Zhai et al, 2019;Zheng et al, 2020). Consistently, microbial communities in the BS have been influenced by hypoxia (Wu et al, 2022), river input (Wang et al, 2021), and heavy metals (Ming et al, 2021). However, the microbial assembly pattern in this highly disturbed ecosystem is largely unknown.…”
Section: Introductionmentioning
confidence: 99%